Pulmonary Complications in Premature Infants Using a Beractant or Poractant for Respiratory Distress Syndrome: A Retrospective Cohort Study - Wong, Kin Lok; Siu, Kiu Lok (American Journal of Perinatology, 2022)
Objective Premature infants are at the risk of developing respiratory distress syndrome (RDS). Beractants and poractants are two commonly used natural surfactants. This retrospective cohort study aims to compare the incidence of pulmonary complications between beractant and poractant treatment groups.Study Design This study evaluated 29 patients treated with beractant and 49 patients treated with poractant. The primary outcome was the incidence of air leak syndrome (ALS) and pulmonary hemorrhage. Secondary outcomes included mortality and pulmonary outcomes, such as mechanical ventilation duration, oxygen dependence duration, fraction of inspired oxygen, and mean airway pressure (MAP) requirement. Logistic regression analyses were conducted to identify independent risk factors for significant primary outcomes.Results No significant difference was found in the demographics between the two groups. A significantly higher incidence of pulmonary hemorrhage was observed in the poractant group (14.3 vs. 0.0%, p = 0.038). The difference in the incidence of ALS between the groups was insignificant (p = 0.536). Logistic regression for the incidence of pulmonary hemorrhage identified coagulopathy as the only significant independent risk factor (odds ratio 39.855, 95% confidence interval [2.912–545.537]; p = 0.006). Secondary outcomes in both treatment groups were similar, except that patients in the poractant group had a higher MAP before surfactant therapy (9 vs. 8 cmH2O, p < 0.001).Conclusion This study showed a significantly higher incidence of pulmonary hemorrhage in the poractant group. Coagulopathy was identified as an independent risk factor for pulmonary hemorrhage. Future long-term prospective studies are essential to establish the temporal and causal relationships between coagulopathy and pulmonary hemorrhage in premature infants receiving surfactant therapy for RDS; hence, there is the need for a screening protocol before surfactant administration.Key Points
Keywords: poractant; beractant; respiratory distress syndrome; pulmonary hemorrhage; air leak syndrome